Development in the surgical treatment of acute appendicitis: A single-center experience - Valentina Pastore; Raffaella Cocomazzi; Angela Basile; Francesco Niglio; Fabio Bartoli (Wolters Kluwer Medknow Publications, 2020)
Purpose: Laparoscopy has become the treatment of choice for acute appendicitis. The aim of the study was to compare open (OA) and laparoscopic (LA) approaches in all forms of acute appendicitis. Methodology: Two hundred and ninety-two children underwent appendectomy (238 LA/54 OA). 3/238 patients required conversion. LA surgical technique has been modified by closing also the distal stump of appendix (DSC) before removing it. Results: Early experience: 130 appendectomy, 44 by OA (34%), and 86 by LA (66%). The mean operative time was similar for both techniques. Complicated appendicitis (CA) was observed in 14 patients (11%). 10 patients treated with OA (10/14 = 71%) and 4 with LA (4/14 = 29%). Complications occurred mainly in the LA group without statistical significance. Late Experience: One hundred and sixty-two appendectomy, 10 OA (6.17%), and 152 LA (93.8%). Thirty-eight children (23.4%) had CA. The mean operative time was lower in LA group without reaching statistical significance. Total complication rate (CR) was 7.4%. CR in patients with DSC was null and significantly lower when compared to patients without DSC. Conclusion: Our results demonstrated that nearly all cases of appendicitis may be managed by laparoscopy. Ligature of distal appendiceal stump is a trick that may significantly improve outcomes during LA appendectomy.